Effective Parameters in the Formation of Ni-Nanoparticles - Novinrooz*, A.J.; Shahbahrami, N.; Reyhani, A. (Asian Journal of Chemistry, 2011)
The synthesis of nickel nanoparticles with various grain sizes has been achieved by spontaneous autocatalytic reduction in alcohol-water solution. It was found that, the concentration of NaOH and hydrazine catalysts play significant role in the formation of resultant nanoparticles. Investigations of different samples revealed that, a single phase nickel can be obtained at pH value 13.5 which was supported by XRD and FTIR analyses. The phase structures and morphologies of the Ni-nanoparticles have been carried out by using XRD and SEM. The crystallography studies of the samples indicate that resultant particles were crystalline fcc structure with average diameter sizes about 6.5 nm at room temperature. The nanoparticle sizes decreased by increasing of lattice constant and, increased by raising of the solution temperature from 25-175 ºC. Also, the AAS analyses indicated that the Ni concentration in mixed solution was high at higher catalyst concentration. The SEM images of the samples showed the particle sizes were narrow (ca. 50-80 nm) at pH value 13.5 and solution temperature 25 ºC.